The Investigation of the Dominant Direction of the Fault Structure Using the Radon Method at Mt. Pancar Geothermal Field - Afero, Faruk; Dear, Varuliantor; Husin, Asnawi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The Mt. Pancar geothermal field in Bogor, Indonesia, has been surveyed for radon in soil gas. There were 33 measurement points across the survey area that were separated by 100-200 meters. Through the radon method, this study aims to show the direction of the dominant fault structure based on the distribution of radon values in around observation area. The Radon concentration was measured by RAD 7 Electronic Radon Detector Durridge Company. The study showed the dominant structure was directed southwest-northeast, passing through the manifestation of the red crater. The result of radon soil gas survey performed highest radon concentration near the manifestations which was included survey area was about 10047 Bq⁄m^3. The manifestation was predicted to be controlled by the three faults in the Mt. Pancar geothermal field.